Improving Teacher Competence in Developing Learning Implementation Plans Through Clinical Supervision at SLBN Pembina Province of East Kalimantan - Prasetya, Agus (PT Literasi Nusantara Publisher, 2022)
This research is motivated by the problem of weak teachers in preparing Learning Implementation Plans (RPP). The purpose of this study was to describe the increase in teacher competence in preparing lesson plans through clinical supervision at SLBN Pembina Prov. East Kalimantan, Samarinda City District. This research is a type of School Action Research (PTS) through cycles consisting of 4 stages, namely: planning, implementing, observing, and reflecting. The subjects of this research were two class teachers. Data collection techniques used in this study are: documentation, observation, and interviews. The data analysis used in this study is descriptive quantitative data analysis which originates from observation and evaluation data.